2018
DOI: 10.1016/j.amjmed.2017.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Therapy in Patients with Acute Myocardial Infarction: A Systemic Review and Meta-Analysis

Abstract: This meta-analysis confirms the lack of benefit of routine oxygen therapy in patients with acute myocardial infarction with normal oxygen saturation levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 33 publications
(54 reference statements)
0
10
1
Order By: Relevance
“…This may reflect more recent evidence that the routine provision of supplemental oxygen does not appear to improve outcomes following acute MI. 26,27 The mean self-reported intraoperative FiO 2 administered by specialist anaesthetists in the present survey is lower than the practice patterns suggested from international observational data. A recent observational study of British anaesthetists found that the mean intraoperative FiO 2 administered to adult patients having non-cardiac surgery where an arterial cannula was placed by the treating anaesthetist, was 0.49.…”
Section: Comparison With Previous Studiescontrasting
confidence: 65%
“…This may reflect more recent evidence that the routine provision of supplemental oxygen does not appear to improve outcomes following acute MI. 26,27 The mean self-reported intraoperative FiO 2 administered by specialist anaesthetists in the present survey is lower than the practice patterns suggested from international observational data. A recent observational study of British anaesthetists found that the mean intraoperative FiO 2 administered to adult patients having non-cardiac surgery where an arterial cannula was placed by the treating anaesthetist, was 0.49.…”
Section: Comparison With Previous Studiescontrasting
confidence: 65%
“…The characteristics of AMI include rapid morbidity and high mortality. The key to improving the prognosis of AMI is the restoration of myocardial blood oxygen supply as soon as possible (10). At present, PCI is generally used to alleviate the clinical symptoms of AMI, by dredging the blocked coronary artery to promote the normal blood oxygen supply of the myocardium (11).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were consistent with the results of studies that evaluated the impacts of supplemental oxygen therapy in other clinical settings. Several RCTs and meta-analyses have demonstrated that oxygen therapy does not significantly reduce all-cause mortality, and can even increase the incidence of early myocardial injury and infarct size among AMI patients with normoxemia [8,[10][11][12][13][29][30][31][32][33]. A total of 11 RCTs including 6366 patients with acute stroke showed a nonsignificant increase in mortality at 3, 6, and 12 months in patients who received normobaric oxygen compared with those who received ambient air [34].…”
Section: Discussionmentioning
confidence: 99%